The Effectiveness Of Family Empowerment In Increasing The Independence Of The Daily Living Activities Of Children With Intellectual Disability - Prasaja, Prasaja; Harumi, Linda (Poltekkes Kemenkes Surakarta, 2023)
Background: Intellectual Disability (ID) is a disability characterized by significant limitations in intellectual functioning and adaptive behavior in many social skills and practical daily skills, including activities of daily living (ADL). To train ID children to independently carry out these activities, it is necessary to empower families (increase knowledge, attitudes, and skills of parents in handling ID children at home) so that the handling of ID children can be optimal. The purpose of this study was to analyze the effectiveness of family empowerment through training and monitored home programs on increasing ADL independence for ID children. Methods: This research was conducted using a quasi-experimental one-group pretest and posttest. The data analysis in this study is the Paired Samples T-test. The instrument in this study is WeeFIM (The Functional Independence Measure for Children). Respondent criteria: mild-severe degree of intellectual disability based on the Mental Retardation Screening examination, ID child's parents are willing and committed to following research procedures, ID child's parents are able to read and can understand the contents of the module (minimum junior high school graduates). Results: Mean value after intervention = 103.21 (> mean before intervention = 96.54) and statistically significant (p = 0.000). It showed that family empowerment (training and monitored home programs) significantly increased the independence of children with intellectual disabilities. Conclusion: The family empowerment program (training and monitored home programs) is a cheap, easy, and effective program for ID children, and it can be applied to all families of ID children.